WNT4 Acts Downstream of BMP2 and Functions via β-Catenin Signaling Pathway to Regulate Human Endometrial Stromal Cell Differentiation - Li, Quanxi (Endocrine Society, 2013)
Differentiation of endometrial stromal cells into decidual cells is a prerequisite for successful embryo implantation. Our previous studies in the mouse have shown that bone morphogenetic protein 2 (BMP2), a morphogen belonging to the TGFβ superfamily, is essential for this differentiation process. BMP2 is markedly induced in human primary endometrial stromal cells (HESCs) as they undergo differentiation in response to steroid hormones and cAMP. The present study was undertaken to identify the BMP2-mediated molecular pathways in primary cultures of HESCs during decidualization. Using gene expression profiling, we identified wingless-related murine mammary tumor virus integration site 4 (WNT4) as a target of BMP2 regulation during decidualization. Attenuation of WNT4 expression in HESCs by small interfering RNA administration greatly reduced BMP2-induced stromal differentiation. Additionally, adenovirus-mediated overexpression of WNT4 in HESCs markedly advanced the differentiation program, indicating that it is a key regulator of decidualization. The stimulatory effect of WNT4 was accompanied by the accumulation of active β-catenin in the nuclei of decidualizing stromal cells, indicating the involvement of the canonical WNT signaling pathway. Functional inhibition of WNT4/β-catenin pathway by Dickkopf-1, an inhibitor of the canonical WNT signaling, or small interfering RNA-mediated silencing of β-catenin expression, greatly reduced the BMP2- and WNT4-induced decidualization. Gene expression profiling revealed that Forkhead box protein O1, a forkhead family transcription factor and previously reported regulator of HESC differentiation, is a common downstream mediator of both BMP2 and WNT4 signaling. Taken together, these studies uncovered a linear pathway involving BMP2, WNT4/β-catenin, and Forkhead box protein O1 that operates in human endometrium to critically control decidualization.